2012
DOI: 10.1136/jnnp-2011-301590
|View full text |Cite
|
Sign up to set email alerts
|

Ten year survival and outcomes in a prospective cohort of new onset Chinese Parkinson's disease patients

Abstract: 10 years into PD, a significant proportion of patients developed dopa resistant motor and non-motor features. Older onset, PIGD type, PIPon and dementia had a negative impact on survival. Standardised mortality ratio was 1.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 30 publications
9
97
4
1
Order By: Relevance
“…Five studies were inception cohorts (studies recruiting only patients at or near diagnosis) [5,11,12,16,19] and nine were non-inception cohorts (e.g. prevalence studies, consecutive series) [10, 13-15, 17, 18, 20-22].…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies were inception cohorts (studies recruiting only patients at or near diagnosis) [5,11,12,16,19] and nine were non-inception cohorts (e.g. prevalence studies, consecutive series) [10, 13-15, 17, 18, 20-22].…”
Section: Included Studiesmentioning
confidence: 99%
“…Thirteen studies were hospital based [5,10,[12][13][14][15][16][17][18][19][20][21][22] and one was community based [11]. Nine studies were retrospective [5,12,14,15,17,18,[20][21][22] and five were prospective [10,11,13,16,19]. One study was published before the introduction of levodopa [5], three straddled its introduction [15,18,20] and the rest were carried out when levodopa was widely available [10-14, 16, 17, 19, 21].…”
Section: Included Studiesmentioning
confidence: 99%
“…[1][2][3] The Sydney Multicenter Study -the longest published follow-up of a newly diagnosed PD cohort to date -found that 83% of those alive at 20 years had developed PDD and 75% developed PDD before death,…”
Section: Pd Dementiamentioning
confidence: 99%
“…A spectrum of cognitive deficit is associated with PD, from subjective cognitive decline (PD-SCD) to mild cognitive impairment (PD-MCI) and dementia (PDD). Longitudinal cohort studies have demonstrated that approximately half of those diagnosed with PD for 10 years develop PDD, [1][2][3] while the point prevalence of dementia among those with PD is between 35% and 30%. 4 In context, PDD accounts for 3%-4% of dementia of all types within the general population, a much smaller percentage than Alzheimer's disease (AD; 50%-70%) or vascular dementia (15%-25%).…”
Section: Introductionmentioning
confidence: 99%
“…As the disease progresses, new symptoms emerge that are levodopa-resistant and become the dominant causes of death and disability. 8,9 Modern health care also underscores patient-centred care and patient empowerment, which highlights patient preferences and their own decision-making. Hence, it is generally accepted that a multidisciplinary health care model is preferable to a monodisciplinary model.…”
Section: Multidisciplinary Care With Deep Brain Stimulation For Parkimentioning
confidence: 99%